Determine of the nira water viscosity by using video based laboratory falling ball method with tracker software - Rianita Bela Islami; Lalu A. Didik; Bahtiar Bahtiar (Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to determine the viscosity of nira water using a falling ball method based on a video based laboratory with tracker software. This type of research is experimental research with a quantitative approach. The viscosity of nira water is measured by varying the temperature, concentration and duration of fermentation. The temperature varied, namely 160C, 270C and 820C. The concentrations were varied by comparing the viscosity coefficient value of pure nira water, nira water added with coconut water and mineral water. And for the fermentation time of the nira water was varied for 7 days, 9 days and 11 days of fermentation. The nira water with varying temperature, concentration and fermentation time has different coefficient values for the nira water. The nira water given the highest temperature has the lowest viscosity coefficient value. And the nira water with the highest concentration has the highest viscosity coefficient value as well. And the longest fermented juice showed the lowest value of the viscosity coefficient of nira water. And from the results of my interviews with nira water farmers in the village regarding the good viscosity coefficient value of nira water, it can be taken from the value of viscosity coefficient of pure nira water, as researchers also examined in this research. Because researchers saw to harvest nira water directly from the tree for research on pure nira water.